Shock formation in magnetised electron–positron plasmas: mechanism and timing - A Stockem Novo; A Bret; U Sinha (New Journal of Physics, 2016)
The shock formation process in electron–positron pair plasmas is investigated in the presence of an ambient perpendicular magnetic field. In initially unmagnetised plasmas, which are dominated by the Weibel or filamentation instability, the shock formation time is a multiple of the saturation time of the linear instability. While in weakly magnetised plasmas the mechanism is still the same, higher magnetisations induce synchrotron maser modes such that the shock formation is dominated by magnetic reflection. As a consequence the formation times are reduced. The focus is on the detailed picture of the particle kinetics, in which the transition between Weibel and magneto-hydrodynamic shocks can be clearly identified.